Tradition and change in the age of Improvement: a study of Argyll tacksmen’s houses in Morvern - Maudlin, Daniel (Proceedings of the Society of Antiquaries of Scotland, 2004)
This paper is an historical and architectural case-study of the remaining Argyll tacksmen’s houses in Morvern, built during the first phase of agricultural Improvement between 1754 and 1819. It is argued that this group of buildings represents the last phase of clan warfare in the region, built by tacksmen acting as colonizing agents of Campbell control and polity over relatively recently acquired MacLean territory.